Active Particle Based Selective Transport and Release of Cell Organelles and Mechanical Probing of a Single Nucleus. Issue 22 (4th May 2020) - Wu, Yue; Fu, Afu; Yossifon, Gilad
Abstract: Self‐propelling micromotors are emerging as a promising microscale tool for single‐cell analysis. The authors have recently shown that the field gradients necessary to manipulate matter via dielectrophoresis can be induced at the surface of a polarizable active ("self‐propelling") metallo‐dielectric Janus particle (JP) under an externally applied electric field, acting essentially as a mobile floating microelectrode. Here, the application of the mobile floating microelectrode to trap and transport cell organelles in a selective and releasable manner is successfully extended. This selectivity is driven by the different dielectrophoretic (DEP) potential wells on the JP surface that is controlled by the frequency of the electric field, along with the hydrodynamic shearing and size of the trapped organelles. Such selective and directed loading enables purification of targeted organelles of interest from a mixed biological sample while their dynamic release enables their harvesting for further analysis such as gene/RNA sequencing or proteomics. Moreover, the electro‐deformation of the trapped nucleus is shown to be in correlation with the DEP force and hence, can act as a promising label‐free biomechanical marker. Hence, the active carrier constitutes an important and novel ex vivo platform for manipulation and mechanical probing of subcellular components of potential for single cell analysis. Abstract : It is demonstrated that self‐propelling metallo‐dielectric Janus particles, under an externally applied electric field, can trap and transport deformable cell organelles in a selective and releasable manner. Moreover, electro‐deformation of the trapped nucleus can act as a promising label‐free biomechanical marker. Hence, the Janus particle constitutes an ex vivo platform for manipulation and mechanical probing of subcellular components.